CAUSES OF FUNCTIONAL DECLINE IN ELDERLY HOSPITALIZED PATIENTS RECEIVING EITHER INDIVIDUAL OR EXCLUSIVE REHABILITATION THERAPY: A COHORT STUDY (International Journal of Physiotherapy, 2018)
Background: Recently, exclusive rehabilitation therapy was introduced to prevent functional decline due to hospital-associated deconditioning by managing older inpatients’ activities of daily living in Japan. However, this type of therapy does not provide one-on-one exercises similar to individual rehabilitation therapy. This study aimed to report the present ward conditions and the causes of the functional decline in elderly patients receiving individual or exclusive rehabilitation therapy.Methods: A total of 1,636 inpatients, aged 65 years or older, were included in the study. Barthel Index at admission and discharge was assessed prospectively to analyze functional decline. We further analyzed the causes of functional decline by investigating the inpatient’s medical records.Results: Forty-three inpatients (2.6%) had functional decline during hospitalization. There were no significant differences in age, Barthel Index at the time of admission, and the type of clinical department between inpatients with and without functional decline. The functional decline rate in individual rehabilitation therapy was 8.2%, which was significantly higher compared to exclusive rehabilitation therapy (0.8%). The most common causes of functional decline were a pain, low postoperative physical fitness, malignant neoplasm, and new-onset cerebral stroke.Conclusion: We report the present ward conditions in elderly patients receiving either individual or exclusive rehabilitation therapies. Functional decline was correlated to the inpatients’ disease and conditions. The causes of the functional decline can be classified based on whether rehabilitation was effective or ineffective. If the functional decline was caused by hospital-associated deconditioning, we should address the functional decline by providing appropriate rehabilitation methods.